How do you solve by substitution 3x + 2y = 6 and x + 2y = -6?

2 Answers
Jun 13, 2015

x=6
y=-6

Explanation:

Try this:
enter image source here

Jun 13, 2015

x=6
y=-6

Explanation:

To solve a system by substitution, you need to replace one unknown by a function of the other, using one of the equations.

Example:
x+2y=-6
becomes
x=-2y-6

Then, in the other equation, you replace x with its y-depending expression:

3x+2y=6
becomes
2y-6y-18=6
rarr -4y=24
rarr y=-6

Now that you have the value of y, you can find the value of x:

x=-2y-6
becomes
x=-2*(-6)-6
rarr x=12-6=6